Litho Stabilization of Silty Sands by Crushed Basalt Stones for Their Use in the Base Layers of Pavements - Casimir, Gouafo; Keyangue Tchouata, Jules Hermann; Barthelemy , Ndongo; Djousse Kanouo, Boris Merlain; Mathurin, M. Zoyem Gouafo (European Journal of Applied Sciences, 2022)
This study shows the improvement of the clayey sand of Maka in center Cameroon. This improvement is made with crushed basalt stone of class 0/31.5 mm, for its use in road construction according to the CEBTP of standard. The validation of this litho stabilization method was carried out in determining the plastic index, the optimum water content, the dry densities and the CBR index of the various mixtures. The results of the mixtures made in the laboratory with the choices of the following percentages: 90% silt sand + 10% crushed basalt stones, 85% silt sand + 15% crushed basalt stones, 80% silt sand + 20% of basalt crushed stone and 70% silt sand + 30% crushed basalt stones meets the criteria of the Practical Guide to Pavement Design for Tropical Countries (CEBTP) for the base course of flexible pavements. In fact CBR at 95% OPM has increased from 23% for loamy sand to 47%; 55%; 58% and 64% respectively for the same mixtures. Optimal Proctor water content decreased from 10.1% for silty sand to 10.08%; 10%; 9.60% and 8.0 % respectively for the same mixtures. The plastic index went from 9.8 % for silty sand to 9.6 %; 9.4 %; 8.9 % and 5.8 % respectively for the same mixtures, these values above indicates weakly clayey mixtures according to Guide of road earthworks (GTR). Moreover, we were able to observe that the granulometric curves of the mixtures of clayey sands with basaltic gravels extend beyond the reference spindles. These mixtures cannot be used as a base course for rigid pavements. Stabilization must be improved with at least 1% cement for rigid pavements. The increase in dry density from 1.75 to 2.024, more than compensates for the relative loss of optimal water content and thus allows the mixture to have a better bearing capacity for compaction than non-silt sand improved, all these properties are greater than those of natural clay sand. This confirms that the addition of crushed basalt makes clayey sand more rigid and dense.